Soil microarthropods support ecosystem productivity and soil C accrual: Evidence from a litter decomposition study in the tallgrass prairie. (January 2016) - Soong, Jennifer L.; Vandegehuchte, Martijn L.; Horton, Andrew J.; Nielsen, Uffe N.; Denef, Karolien; Shaw, E. Ashley; de Tomasel, Cecilia Milano; Parton, William; Wall, Diana H.; Cotrufo, M. Francesca
Abstract: Soil fauna have been found to accelerate litter decomposition rates across many ecosystems, but little is known about their impact on soil organic matter formation during decomposition and their influence on ecosystem carbon and nitrogen cycling during this process. In a three-year litterbag-free decomposition study, we suppressed microarthropod abundance by 38% and tracked the fate of 13 C- and 15 N-labeled litter into different soil organic matter fractions and the microbial community. Microarthropod suppression slowed litter mass loss and decreased litter carbon input into the soil and soil microbes during the first 18 months of decomposition. The microarthropod suppression did not alter the total amount of carbon and nitrogen incorporated in the soil after complete surface litter mass loss. However, lower early-stage microbial carbon uptake due to lower early-stage litter inputs to the soil, as well as a significant decrease in the C:N ratio of litter-derived organic matter inputs to the mineral soil fractions, made less nitrogen available for plant uptake in the microarthropod suppression treatment. Thus, the acceleration of early-stage, more labile litter inputs to the soil altered the timing and availability of carbon and nitrogen inputs to the soil. A simulation of these effects on the tallgrass prairie ecosystem using the DayCent model predicts lower net primary productivity and lower total soil C and N mineralization when soil microarthropods are less abundant. Our results highlight the importance of soil microarthropods for ecosystem functioning through their role in transforming decomposing litter organic matter into soil organic matter and the feedback of this process to ecosystem productivity and soil C sequestration. Highlights: 3-year 13 C and 15 N labeled litter decomposition study in situ . Microarthropods altered timing and process of SOM formation during decomposition. Microarthropods decreased the C:N of SOM formed and increased N availability. Microarthropods increased initial PLFA C uptake but not ultimate C sequestration. DayCent simulation reveals the role of microarthropods in NPP and C sequestration.